2018
DOI: 10.1016/j.celrep.2018.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Von Hippel-Lindau Protein Is Required for Optimal Alveolar Macrophage Terminal Differentiation, Self-Renewal, and Function

Abstract: SummaryThe rapid transit from hypoxia to normoxia in the lung that follows the first breath in newborn mice coincides with alveolar macrophage (AM) differentiation. However, whether sensing of oxygen affects AM maturation and function has not been previously explored. We have generated mice whose AMs show a deficient ability to sense oxygen after birth by deleting Vhl, a negative regulator of HIF transcription factors, in the CD11c compartment (CD11cΔVhl mice). VHL-deficient AMs show an immature-like phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
(56 reference statements)
2
25
0
Order By: Relevance
“…We have shown that absence of VHL caused glycolytic upshift, impaired mitochondrial respiration capacity, and altered signature gene expression of AMs in a HIF1α-dependent manner. Interestingly, one recent study has shown that VHL plays a critical role in AM terminal differentiation, self-renews, and functions at steady state by using the Vhl fl/fl CD11c -Cre mice (Izquierdo et al, 2018). Consistently, we detected foamy AM morphology, abnormal terminal differentiation markers, and impaired proliferation during inflammation upon loss of VHL.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that absence of VHL caused glycolytic upshift, impaired mitochondrial respiration capacity, and altered signature gene expression of AMs in a HIF1α-dependent manner. Interestingly, one recent study has shown that VHL plays a critical role in AM terminal differentiation, self-renews, and functions at steady state by using the Vhl fl/fl CD11c -Cre mice (Izquierdo et al, 2018). Consistently, we detected foamy AM morphology, abnormal terminal differentiation markers, and impaired proliferation during inflammation upon loss of VHL.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has revealed an indispensable role of von Hippel-Lindau protein (VHL), a negative regulator of hypoxia-inducible factors (HIFs), in the terminal differentiation of AMs [34]. Self-renewal capacity was severely impaired in AMs that were selectively depleted of Vhl gene.…”
Section: Monocytes and Tissue-resident Macrophages In The Normal Lmentioning
confidence: 99%
“…In contrast to Ssu72-deficient AMs, Ssu72-deficient IMs showed no defects in the cell cycle or cyclin expression ( Fig 3, D and E). Results from the in vivo BrdU incorporation assay 19 in LysM-CreSsu72 fl/fl mice showed that the rate of BrdU uptake in mature AMs at day 1 versus at day 7 after BrdU injection was lower than in LysM-Cre mice. This indicated that turnover of mature Ssu72-deficient AMs is lower than that of mature WT AMs (Fig 3, F).…”
Section: Ssu72 Regulates Cellular Homeostasis and The Function Of Matmentioning
confidence: 91%